Biotransformation of Soluble Microbial Products (SMPs) in an Anaerobic Baffled Reactor (ABR) - Soh, Annie Yan Ni (2019)
The change in SMP composition of an ABR operating at 24-hour HRT treating synthetic wastewater of medium-strength glucose feed was analysed using SPE-GC-MS. The results showed that alkanes and alkenes generally saw an increase down the compartments of the ABR. The number of esters identified on the first three sampling times when glucose feed was 2 gCOD/L, were only different by 2-3 compounds. On day 96 when the ABR was approaching a pseudo steady state, the number of detected ester compounds increased, with 8 out of 11 esters increasing in concentration by 5-6 times. A 1.5-3-fold increase in the number of alkane, alkene, ester, acid, aromatic and nitrogenous compounds, and other unidentified compounds, were observed when the feed concentration doubled. The possible reasons for the formation of the compounds is discussed, using established pathways from the well-researched areas in natural product synthesis and metabolism in plants, fungi, algae, and pure strains of microorganisms.